Report of the Committee on Confederate Relations relative to sequestration of property : March 25, 1863 (Document (Virginia. General Assembly. Senate) ;, 1863)
March 25, 1863 Report of the Committee on Confederate Relations regarding the constitutionality of the Confederate government to sequestrate property owned by "alien enemies." The committee determined that no such power exists and its senators should seek to obtain a repeal of this act.